Bacteria‐Responsive Self‐Assembly of Antimicrobial Peptide Nanonets for Trap‐and‐Kill of Antibiotic‐Resistant Strains. (29th November 2022) - Tram, Nhan Dai Thien; Xu, Jian; Mukherjee, Devika; Obanel, Antonio Eduardo; Mayandi, Venkatesh; Selvarajan, Vanitha; Zhu, Xiao; Teo, Jeanette; Barathi, Veluchamy Amutha; Lakshminarayanan, Rajamani; Ee, Pui Lai Rachel
Abstract: Bacterial trapping using nanonets is a ubiquitous immune defense mechanism against infectious microbes. These nanonets can entrap microbial cells, effectively arresting their dissemination and rendering them more vulnerable to locally secreted microbicides. Inspired by this evolutionarily conserved anti‐infective strategy, a series of 15 to 16 residue‐long synthetic β‐hairpin peptides is herein constructed with the ability to self‐assemble into nanonets in response to the presence of bacteria, enabling spatiotemporal control over microbial killing. Using amyloid‐specific K114 assay and confocal microscopy, the membrane components lipoteichoic acid and lipopolysaccharide are shown to play a major role in determining the amyloid‐nucleating capacity as triggered by Gram‐positive and Gram‐negative bacteria respectively. These nanonets displayed both trapping and killing functionalities, hence offering a direct improvement from the trap‐only biomimetics in literature. By substituting a single turn residue of the non‐amyloidogenic BTT1 peptide, the nanonet‐forming BTT1‐3A analog is produced with comparable antimicrobial potency. With the same sequence manipulation approach, BTT2‐4A analog modified from BTT2 peptide showed improved antimicrobial potency against colistin‐resistant clinical isolates. The peptide nanonets also demonstrated robust stability against proteolytic degradation, and promising in vivo efficacy and biosafety profile. Overall, these bacteria‐responsive peptide nanonets are promising clinical anti‐infective alternatives for circumventing antibiotic resistance. Abstract : A series of synthetic β‐hairpin antimicrobial peptides are designed with the ability to self‐assemble into nanonets selectively in the presence of bacteria. They can simultaneously entrap and kill the bacteria. Both trapping and killing functionalities can be modulated through rational sequence manipulation. These bacteria‐specific and proteolytically robust nanonets offer an innovative anti‐infective approach to tackle antibiotic resistance.